Pola Pengobatan Fluor Albus Di Rumah Sakit Umum Pusat Nasional Dr Cipto Mangunkusumo Serta Faktor-Faktor Yang Mempengaruhinya (Analisis Data Rekam Medik Tahun 2006-2007) - Rusdi, Numlil Khaira; Trisna, Yulia; Soemiati, Atiek (Majalah Ilmu Kefarmasian, 2008)
The objectives of this study were to know (1) Patients’ characteristics (2) The most etiology of leucorrhoea (3) Association between clinical manifestations or genital symp-toms with etiology of leucorrhoea (4) Therapy management of leucorrhoea by obstet-ric-gynecologist and venereologist (5) Factors influenced the treatment of leucorrhoea (6) Compliance with hospital therapeutic guidelines. The study was cross sectional and retrospective. A total of 437 patients hospitalized from January 2006-December 2007 were included. The results showed that leucorrhoea was found in 17,6% of patients at sexually transmitted disease clinic and 82,4% of patients at obstetric-gynecology clinic. The majority of patients were in productive age, married, and housewife, with most of genital symptoms were pruritus and curd-like vaginal dis-charge. The most of etiology leucorrhoea in this study was candidiasis. Statistically, there were association between genital symptoms with candidiasis and bacterial vaginosis (p<0,05). The specific genital symptoms of candidiasis were pruritus and curd-like vaginal discharge, whereas for bacterial vaginosis were homogeneous and increased vaginal discharge. There were different treatments of vaginal discharge be-tween obstetric-gynecologist and venereologist. For candidiasis, the obstetric-gyne-cologist preferred to use fluconazole, and metronidazole+nystatin (Flagistatin®); whereas the venereologist used clotrimazole and itraconazole. For bacterial vaginosis, obstet-ric-gynecologist used clindamycin and metronidazole+nystatin (Flagistatin®), while venereologist preferred to use metronidazole. For trichomoniasis there was no different treatment between obstetric-gynecologist and venereologist. In pregnancy, antibiot-ics used to treat leucorrhoea were clindamycin, fluconazole, metronidazole+nystatin (Flagistatin®), metronidazole, and nystatin. Prescribing compliance with the hospi-tal therapeutics guidelines were 37,8%. The type of antibiotics used were azitromycin, clindamycin, clotrimazole, doxycycline, fluconazole, itraconazole, ketoconazole, and metronidazole. Statistics analysis by Logistic regression (Cl 95%) showed that factors influenced the treatment of leucorrhoea included genital symptoms (OR = 0,975), risk factors (OR = 0,917), etiology (OR = 1,103), and comorbid diseases (OR = 1,387).